Tolerância ao déficit hídrico em mudas de Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) produzidas a partir de sementes hidrocondicionadas para projetos de regeneração da caatinga - Melo, Alyne Fontes Rodrigues de (2018)
The process of seed imbibition in species of Caatinga dry forest does not occur continuously because of the scarcity and irregularity of the rains, besides the high temperatures. However, this discontinuous hydration may favor seedling germination and survival in this environment. This study evaluated the effect of seed hydropriming on germination, growth and ecophysiological parameters of plants under water deficit. After going through the process of overcoming of integument dormancy with immersion in sulfuric acid for 60 minutes, the Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) seeds were submitted to 0, 1, 2 and 3 cycles of hydration and dehydration (HD) and placed to germinate, resulting in plants which, after acclimation for 15 days, were subjected to suspension watering intervals of seven (E7) and fourteen days (E14) and their growth in height and diameter and number of leaves evaluated weekly. Biweekly was performed collecting a leaf for analysis of Ecophysiological parameters, such as relative water content (TRA), accumulation of solutes (carbohydrates, protein and proline). The leaf water potential was measured after 45 days and at the end of the experiment, corresponding to 75 days. Germination was favored by one and two hydropriming HD cycles whose seeds had higher speed and shorter timing to germinate. The height of the plants submitted to 2C was higher than the seedlings of the control treatment. Although, under water stress conditions, there was no difference in growth, the passage through HD cycles conferred some kind of advantage that propagates from the seed to the next phase. The species showed a general capacity of tolerance to drought, osmotic-adjusting, reducing leaf water potential and thus maintained the turgor of the cells. In particular, the 3C plants were able, during the whole experiment, to keep the TRA of the stressed plants equal to the control plants through the accumulation of the osmoprotective solutes. The present study confirmed that the hydropriming of the seeds favors the germination and the initial development of the E. contortisiliquum seedlings and can be used as pregerminative treatment for the use of the species in Caatinga regeneration projects.